2022
DOI: 10.1097/inf.0000000000003585
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Single-dose Azithromycin on Pneumococcal Carriage and Resistance: A Randomized Controlled Trial

Abstract: We evaluated antibiotic resistance selection in Streptococcus pneumoniae isolates from children participating in an individually randomized trial of single-dose azithromycin versus placebo. After 14 days, the prevalence of resistance to erythromycin, oxacillin, and clindamycin was elevated in the azithromycin versus placebo group. There was no difference at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Selection for macrolide resistance has been observed in studies of both individual and mass distribution of azithromycin for trachoma and childhood mortality, although any selection for macrolide resistance typically declines after selection pressure is removed. [28][29][30] It is likely that the single dose of azithromycin led to short-term increases in macrolide resistance in the present study; however, any clinical implications of this are unclear. A companion trial to the present work found transient effects of azithromycin on pneumococcal macrolide resistance that returns to baseline levels by 6 months.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Selection for macrolide resistance has been observed in studies of both individual and mass distribution of azithromycin for trachoma and childhood mortality, although any selection for macrolide resistance typically declines after selection pressure is removed. [28][29][30] It is likely that the single dose of azithromycin led to short-term increases in macrolide resistance in the present study; however, any clinical implications of this are unclear. A companion trial to the present work found transient effects of azithromycin on pneumococcal macrolide resistance that returns to baseline levels by 6 months.…”
Section: Discussionmentioning
confidence: 73%
“…A companion trial to the present work found transient effects of azithromycin on pneumococcal macrolide resistance that returns to baseline levels by 6 months. 28 The consequences of transient increases in macrolide resistance in potentially pathogenic organisms are not well characterized. Previous trials of mass azithromycin distribution have not found reductions in efficacy over time, suggesting that any selection for antimicrobial resistance does not reduce efficacy for preventing mortality, and macrolides are rarely used as first-line therapy in the study area.…”
Section: Discussionmentioning
confidence: 99%